2013
DOI: 10.1128/mcb.00618-13
|View full text |Cite
|
Sign up to set email alerts
|

Deacetylase Rpd3 Facilitates Checkpoint Adaptation by Preventing Rad53 Overactivation

Abstract: bThe DNA damage checkpoint is tightly controlled. After its activation, the checkpoint machinery is inactivated once lesions are repaired or undergoes adaptation if the DNA damage is unable to be repaired. Protein acetylation has been shown to play an important role in DNA damage checkpoint activation. However, the role of acetylation in checkpoint inactivation is unclear. Here we show that histone deacetylase Rpd3-mediated deacetylation of Rad53 plays an important role in checkpoint adaptation. Deletion of Rp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 40 publications
1
7
0
Order By: Relevance
“…To assess the impact of Cmr1 and INQ on the DNA damage checkpoint, we performed a checkpoint adaptation assay using the cdc13-1 allele, which causes uncapping of telomeres and DNA-damage checkpoint activation at the restrictive temperature 34 . We included in the assay a mutant of the INQ component Rpd3, which has previously been reported to be adaptation defective 35 . After growth at the restrictive temperature for 24 h, the number of cell bodies was counted.…”
Section: Resultsmentioning
confidence: 99%
“…To assess the impact of Cmr1 and INQ on the DNA damage checkpoint, we performed a checkpoint adaptation assay using the cdc13-1 allele, which causes uncapping of telomeres and DNA-damage checkpoint activation at the restrictive temperature 34 . We included in the assay a mutant of the INQ component Rpd3, which has previously been reported to be adaptation defective 35 . After growth at the restrictive temperature for 24 h, the number of cell bodies was counted.…”
Section: Resultsmentioning
confidence: 99%
“…The phenotypes of rpd3Δ and sin3Δ mutants diff er due to diff erent activation of Rad53 kinase, which may be due to deacetylation of Rad53 by Rpd3 deacetylase. Our fi ndings revealed that the contribution of deacetylation of Rad53 kinase makes a signifi cant contribution to the regulation hyperactivation RNR complex after UV irradiation [32]. Based on the data obtained, we assumed that the Him1 protein is a new histone chaperone participating in the repair assembly of chromatin.…”
Section: Introductionmentioning
confidence: 66%
“…Many roles for Rpd3 have been described; including in control of DNA replication ( 37 , 38 , 39 ), transcriptional regulation ( 45 , 46 ) and the DNA damage response ( 47 , 48 ). Further work will therefore be required to understand how Rpd3’s role in gene expression homeostasis relates to its other functions.…”
Section: Discussionmentioning
confidence: 99%